Cooperative antioxidative effects of zein hydrolysates with sage (Salvia officinalis) extract in a liposome system. (1st May 2017) - Li, Yuanyuan; Liu, Haotian; Han, Qi; Kong, Baohua; Liu, Qian
Highlights: Zein hydrolysates and sage extract can synergistically inhibit lipid oxidation. Liposomes with ZH and SE reduced the particle mean diameters and improved stability. Sufficient adsorption of the complex onto the ZH-SE liposome interface was observed. A more compact cross-linked network structure was formed in the ZH-SE liposome. Abstract: This study investigated the cooperative antioxidative effects of sage extract (SE) and zein hydrolysates (ZH). The combination of 3 mg/ml ZH and 10 μg/ml SE exhibited a significant synergism in inhibition of the formation of thiobarbituric acid-reactive substances and provided superior protection of liposomes against oxidation. Zeta-potential results revealed that the interactions between liposomes and ZH were electrostatic interactions. Particle size determination further proved that ZH and SE added to oxidized liposomes significantly decreased the mean particle size. Confocal laser scanning microscopy revealed that when ZH was present in the liposome oxidizing system, the droplet sizes were obviously decreased compared to oxidized samples. ZH dispersed more uniformly and the interfacial membrane was more compact in the ZH-SE liposome. Transmission electron microscopy conveyed that the ZH-SE complex around the liposome particles could form a denser network structure, preventing radicals and oxidants from the approach of the liposomes.